Audit Menggunakan COBIT 5 Domain DSS pada SIAKAD Universitas Merdeka Malang - Agung Surya Putra; Elmo Raditya Sambhodo; Fariz Mahardhika Aisfa; Muhammad Salfian Nur; Mochammad Aldi Priyanta (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
This study conducted an audit of the Academic Information System (SIAKAD) of the University of Merdeka Malang using the COBIT 5 Framework, especially in the domain of deliver, service, and support (DSS). This audit aims to assess the effectiveness, security, and efficiency of information systems in supporting the academic process system. The data collection method used is surveys and interviews with resource persons. 54 respondents consisting of system managers, staff and siakad users. The results of the analysis show that the maturity level of the Academic Information System (SIAKAD) is at level 4 (managed and measurable), with an average score of 3.71. Although in the good category, there is still a gap between the expected level of maturity and the current level. Some areas that must be considered are suboptimal problem documentation, improved system security measures, and lack of an automatic notification system to facilitate communication between system managers or admins and users. The results of this audit are expected to be a reference for Academic Information System managers in improving the performance of the information system as a whole, so that it can support the academic process more effectively, efficiently and safety.